The Agricultural Industry in Belarus: Yesterday, Today, and Tomorrow. Issue 6 (2nd June 2016) - Zayats, L.K.
Abstract : This article presents the features of development dynamics in the Belarusian agricultural sector since the creation of the sovereign state. The article analyzes the stages in the country's agribusiness development as implemented through targeted state programs and considers the prospects for further development of the agricultural sector.